Photoluminescence of heavily zinc-doped gallium arsenide and gallium indium arsenide grown by low-pressure metal organic vapour phase epitaxy. - Benzaquen, Roberto. (University of Ottawa (Canada), 1991)
Zn-doped, p-type, GaAs and $\rm Ga\sb{0.85}In\sb{0.15}As$ samples grown by low-pressure metal organic vapour phase epitaxy with free carrier concentrations in the range of n = 4.3 $\times$ 10$\sp {\rm cm}\sp{-3}$ (nominally undoped)--p = 1.95 x 10$\sp{20} {\rm cm}\sp{-3}$ at room temperature have been studied by temperature-dependent photoluminescence. At low doping levels, recombinations involving discrete impurity states and free excitons provided measurement of both the 5 K band gap ($E\sb{g}(5)=(1.296\pm0.003)$ eV) and the zinc acceptor binding energy $(E(Zn\sp0)=(0.025\pm0.003)$ eV) in the $\rm Ga\sb{0.85}In\sb{0.15}As$ alloy. At high concentrations, the discrete acceptor levels are replace by an impurity band which merges with the valence band above the Mott$\sp{\lbrack 1\rbrack}$ transition. This gives rise to a density of states band tail extending into the gap and containing both extended and localised states. In the presence of such a high density of impurities, potential fluctuations and interparticle interactions result in a band gap shrinkage $\vert \Delta E\sb{g}\vert$ which has been observed with photoluminescence experiments. A model based on the presence of Kane$\sp{\lbrack 2\rbrack}$ band tails and on the assumption of a constant matrix element for the relevant optical transitions has been fitted to the photoluminescence spectra of heavily doped layers of GaAs and $\rm Ga\sb{0.85}In\sb{0.15}As$ in the range of $p=1.6\times 10\sp $ cm$\sp{-3}-p=1.95\times 10\sp{20}$ cm$\sp{-3}.$ This model provided a good description of the experimental results. The 5 K band gap shrinkage has been found to be $\vert\Delta E\sb{g}\vert=2.7\times 10\sp{-8}p\sp{1/3}$ for GaAs and $\vert\Delta E\sb{g}\vert=1.4\times 10\sp{-8}p\sp{1/3}$ for $\rm Ga\sb{0.85}In\sb{0.15}As$ with $\vert\Delta E\sb{g}\vert$ in Ev and p in cm$\sp{-3}.$
Keywords: Physics, Condensed Matter.